1984
DOI: 10.1021/i200024a024
|View full text |Cite
|
Sign up to set email alerts
|

Mass transfer from fine particles in a stirred vessel. Effect of specific surface area of particles

Abstract: A new method was devised to measure the mass transfer coefficient for fine particles in high concentration. In the concentrated suspension, the mass transfer coefficient and the effect on it of agitation decreased with increasing specific surface area of the particles, although variations in the physical properties of the suspension were negligible. These tendencies could be explained by a theoretical model in which the mass transfer from part of the particle surface was impeded by solute which had diffused fr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
4
2

Year Published

1986
1986
2002
2002

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 6 publications
0
4
2
Order By: Relevance
“…For large particles, Asai et al observed that k SL is proportional to D m 2/3 (mass transfer in laminar boundary layer), while for fine particles k SL is proportional to D m (mass transfer by molecular diffusion). Unlike the result of Yagi et al, no effect of particle concentration was observed by Asai et al in the same range of a specific surface area up to 3000 m 2 /m 3 . Asai et al commented that the rapid mixing method used by Yagi et al is not suitable to measure k SL in fine particles solution, giving erroneous results.…”
Section: Solid−liquid Mass Transfer Between Fine Particles and Liquid...contrasting
confidence: 78%
See 3 more Smart Citations
“…For large particles, Asai et al observed that k SL is proportional to D m 2/3 (mass transfer in laminar boundary layer), while for fine particles k SL is proportional to D m (mass transfer by molecular diffusion). Unlike the result of Yagi et al, no effect of particle concentration was observed by Asai et al in the same range of a specific surface area up to 3000 m 2 /m 3 . Asai et al commented that the rapid mixing method used by Yagi et al is not suitable to measure k SL in fine particles solution, giving erroneous results.…”
Section: Solid−liquid Mass Transfer Between Fine Particles and Liquid...contrasting
confidence: 78%
“…dissolution: benzoic acid in water d P = 0.22−0.43 cm (pellets) Δρ = 0.28 g/cm 3 T = 9−63 cm baffled 6DT; D = 3−21 cm; D / T =0.33; C / T =0.50 300−2000 Sicardi et al dissolution: benzoic acid in water d P = 0.11−0.61 cm Δρ = 0.28 g/cm 3 T = 12.8−22.8 cm baffled 4FBT, 6PTD; D = 4.6−7.3 cm; D / T = 0.19−0.56; C / T = 0.15−0.50 1000 Conti and Sicardi 56 dissolution: benzoic acid in water; ion-exchange resins in NaOH d P = 0.092−0.61 cm Δρ ≈ 0.24−0.28 g/cm 3 T = 12.8−22.8 cm baffled 4FBT, 6PTD; D = 4.6−7.3 cm; D / T = 0.19−0.56; C / T = 0.15−0.50 1000 Yagi et al ion-exchange resin in Ca(OH) 2 −water solution d P = 0.0025−0.0145 cm Δρ ≈ 0.24 g/cm 3 T = 15 cm baffled 6DT; D = 8 cm; D / T = 0.50; C / T = 0.50 490 Lal et al …”
Section: Particle−liquid Mass Transfer Coefficient (K Sl) In Two-phas...mentioning
confidence: 99%
See 2 more Smart Citations
“…(d) feaL remains constant with variations in the porosity of the suspension in spite of the fact that some authors have observed appreciable decreases for specific area of particles larger than 200-500 m"1 (Yagi et al, 1984).…”
Section: Discussionmentioning
confidence: 91%